2021
DOI: 10.1108/ijif-12-2020-0252
|View full text |Cite
|
Sign up to set email alerts
|

Sharīʿah governance and agency dynamics of Islamic banking operations in the Kingdom of Saudi Arabia

Abstract: PurposeThis study aims to investigate and point out the variations of agency theory in the context of Sharīʿah governance in Islamic banking operations in the Kingdom of Saudi Arabia (KSA).Design/methodology/approachThe study followed the approach of quantitative Corporate Governance Index (CGI) by computing the Gov-index (Gompers et al., 2003) and the Gov-score (Brown and Caylor, 2004; Saffieddine, 2009) to examine corporate governance (CG) issues using primary as well as secondary data. The primary data was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The Saudi Arabian Monetary Agency (SAMA) stands as the sole regulatory body that oversees IBs. In a recent survey-based study, Hassan et al (2022) reported that all SAbased IBs, be they fully fledged or with Islamic wings, have an SSB composed of four to five members, which is in conformity with AAOIFI's prerequisite. The SSB members are appointed either by the GA or the BoD (Hassan et al, 2022;Grais and Pellegrini, 2006).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 92%
See 3 more Smart Citations
“…The Saudi Arabian Monetary Agency (SAMA) stands as the sole regulatory body that oversees IBs. In a recent survey-based study, Hassan et al (2022) reported that all SAbased IBs, be they fully fledged or with Islamic wings, have an SSB composed of four to five members, which is in conformity with AAOIFI's prerequisite. The SSB members are appointed either by the GA or the BoD (Hassan et al, 2022;Grais and Pellegrini, 2006).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 92%
“…In a recent survey-based study, Hassan et al (2022) reported that all SAbased IBs, be they fully fledged or with Islamic wings, have an SSB composed of four to five members, which is in conformity with AAOIFI's prerequisite. The SSB members are appointed either by the GA or the BoD (Hassan et al, 2022;Grais and Pellegrini, 2006). The SSB members meet at least once per quarter, and their decisions are made through majority voting.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 92%
See 2 more Smart Citations
“…It is also mentioned that conventional corporate governance and Islamic perspectives have many different points of view. The most important thing is the placement of the ideology of monotheism in the perspective of Sharia against the ideology of rationalism in the conventional perspective (Hassan et al , 2021).…”
Section: Introductionmentioning
confidence: 99%